Nazm Jawen on ‘Ilmu Al-Tajwīd and Qirā’āt A La Pesantren (A Study on Tanwīr al-Qāri fī Kalām al-Bāri’ by KH M. Mundzir Nadzir) - Ahmad Baidlowi (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2019)
The history of Islamic intellectualism in Indonesia has now and then been strongly tied to the role of pesantren and kiai, both of which have always been deeply engaging to the agenda of disseminating Islamic teachings to the society. Their attempts including the use of certain model and styles in producing contributions to the agenda show the unique literary traditions of Nusantara ulama, on the one hand, and constitute a communicative way of delivering their academic thoughts. This article delves into Tanwīr al-Qārī fī Kalām al-Bārī’, a book on tajwīd and qirā’āt by KH M Mundzir Nadzir. Closely reading the book, I find that it indeed explains important points of the two disciplines but does reveal social, moral, spiritual, and even theological stances of its author. The locality appears here and there in varying forms, including idioms, and thus attests the dynamic of pesantren’s intellectualism in dealing with local context while introducing and keeping survive Islamic teachings in Indonesian context.[Sejarah intelektualisme Islam di Indonesia tidak bisa dilepaskan dari peran pesantren dan para kiai yang selalu berjuang menyampaikan ilmu-ilmu Islam kepada masyarakat. Upaya para kiai menggunakan gaya atau model tertentu dalam menuliskan karya intelektualnya bukan saja memperlihatkan nuansa sastra khas pesantren yang indah, namun juga menjadi salah satu cara yang komunikatif dalam menyampaikan pesan- pesan ilmiahnya. Artikel ini akan mengkaji Kitab Tanwīr al-Qāri fī Kalām al-Bāri’ KH M. Mundzir Nadzir, yang merupakan karya ulama pesantren tentang Ilmu Tajwid dan Qiraat. Artikel ini mengungkap nilai-nilai yang dibangun oleh penulis bersamaan dengan penjelasan mengenai pengetahuan ilmu tajwid dan qiraat. Dengan menganalisis isi buku, tulisan ini menemukan bahwa, sekalipun Tanwīr al-Qāri fī Kalām al-Bāri’ karya KH M. Mundzir Nadzir memang membahas ilmi tajwid dan qira’at, namun pesan-pesan sosial, moral dan spiritual dengan jelas ditemukan di sana. Aspek lokal dalam karya yang menggunakan Naz}m  Jawen ini memperlihatkan intelektualisme Pesantren yang dinamis dalam rangka pengembangan keilmuan Islam.]